Lung volume reduction for emphysema - Shah, Pallav; Herth, Felix (The lancet. Respiratory medicine, 2017)
Summary: Advanced emphysema is a lung disease in which alveolar capillary units are destroyed and supporting tissue is lost. The combined effect of reduced gas exchange and changes in airway dynamics impairs expiratory airflow and leads to progressive air trapping. Pharmacological therapies have limited effects. Surgical resection of the most destroyed sections of the lung can improve pulmonary function and exercise capacity but its benefit is tempered by significant morbidity. This issue stimulated a search for novel approaches to lung volume reduction. Alternative minimally invasive approaches using bronchoscopic techniques including valves, coils, vapour thermal ablation, and sclerosant agents have been at the forefront of these developments. Insertion of endobronchial valves in selected patients could have benefits that are comparable with lung volume reduction surgery. Endobronchial coils might have a role in the treatment of patients with emphysema with severe hyperinflation and less parenchymal destruction. Use of vapour thermal energy or a sclerosant might allow focal treatment but the unpredictability of the inflammatory response limits their current use. In this Review, we aim to summarise clinical trial evidence on lung volume reduction and provide guidance on patient selection for available therapies.
Published online: 29 September 2016
Gesehen am 20.07.2018